Performance Test of Elephant Grass Crushing Machine for Cattle Feed In Mertak Village, Pujut District, Lombok Tengah Regency - Andrean, Hery; Murad; Amuddin; Puspitasari, Isnaini (J-AGENT (Journal of Agricultural Engineering and Technology), 2024)
This study aims to determine the process of enumeration on a grass chopper machine, knowing the motor power required for a grass chopper, knowing how much fuel the machine needs to chop grass, knowing the length of time for chopping grass, and knowing the rotational speed of the chopper. This research method is experimental by conducting direct testing in the field. Data analysis was carried out using a mathematical approach to complete the mathematical calculation model which was processed using Microsoft Excel. The results showed that the energy available in this chopper was 5.5 HP, while the power used was 1.91 HP. The highest fuel consumption is at 15 Kg material weight of 1.60 Liter/hour, and the lowest is at 5 Kg material weight is 0.80 Liter/hour. The highest chopping capacity was at material weight of 5 Kg at 200 Kg/hour, while the lowest counting capacity was at material weight to 15 Kg at 166 Kg/hour. The highest efficiency based on the machine's ability to transmit power occurs at a weight of 15 Kg, which is 65.05%, while the lowest efficiency is at a weight of 5 Kg, which is 61.21%. The highest efficiency based on fuel consumption occurs at material weight of 5 Kg, namely 41.67%, while the lowest efficiency occurs at material weight of 15 Kg, namely 20.84%.